رتوج اللفائفي والصائم المكتسبة - قاسم, فؤاد (Latakia University Journal -Medical Sciences Series, 2019)
رتوج اللفائفي والصائم المكتسبة هي أمراض نادرة يتراوح معدل حدوثها بين (05-1.4)%، وتكون رتوج الصائم أكثر شيوعاً وأكبر حجماً من رتوج اللفائفي, وهي رتوج متعددة غالباَ. غير أن مضاعفاتها ليست بالاستثنائية (6-13)% مع نسبة وفيات يمكن أن تصل إلى 40% من نسبة المصابين عند المسنين. وأهم المضاعفات هي: 1- التهاب الرتج 16.66%. 2- الانثقاب 11.11%. 3- انسداد الأمعاء الحاد 5.55%. 4- النزف الهضمي 5.55% والذي غالباً مايكون كتلياً (غزيراَ) ونادراً بشكل خفي. 5- أسواء الامتصاص (سوء امتصاص الدسم – نقص البروتينات – فقر دم كبير الكريات). 6- الأورام الهضمية مجهولة السبب. علاج رتوج الأمعاء الدقيقة لا يكون جراحياً إلا عندما تترافق بمضاعفات. ويرتكز العلاج الوقائي للمضاعفات على إجراءات الصحة الغذائية لمقاومة ركود الدم وارتفاع الضغط المعوي (مضادات التشنج، المطهرات المعوية، نظام غذائي قليل الفضلات) والإنتان (مضادات حيوية فموياً). Acquired Jejineum and Ilieus's diverticulum's are rare diseases. They occure in 0.5-1.4%, Jejineum's diveticulms are more unouncing and larger than Ilieues's diverticulms. Its complications are 6-13% and its mortality reaches to 40% from older patients. The most important of complications are: diverticulitis 16.66%. Perforation 11.11%. Acute intestinal obstruction 5.55%. Peptic bleeding 5.55%, this is common massive and rarely. Malabsorbtions (malabsorbtion of fat, hypoprotinemia, Macro anemia). Unknown Peptic tumers. The treatment of intestinal diverticulm is conservative, but it becomes surgical when the complications occur. Protective treatment of complications depends on feeding health's measures against stasis and intestinal Hyperpressure (Antispasmolitic,Intestinal disinfectants, reside free diet) and infection (oral antibiotics).